Hubungan Peran Tenaga Kesehatan dengan Perilaku Masyarakat dalam Pencegahan Demam Berdarah Dengue di Wilayah Puskesmas Purwosari - Yully Kurniawati; Mulyaningsih Mulyaningsih (Pusat Riset dan Inovasi Nasional, 2025)
Jajar Village has been identified as the area with the highest risk of Dengue Hemorrhagic Fever (DHF) within the Purwosari Health Center Work Area. Several environmental and demographic factors contribute to this elevated risk, including the village’s proximity to a river, high population density, presence of stagnant water that facilitates mosquito breeding, and scattered waste that serves as additional breeding sites. Although health workers have implemented various DHF prevention programs, their execution has not yet reached optimal effectiveness. Objective: This study aimed to determine the relationship between the role of health workers and community behavior in preventing DHF in the Purwosari Health Center Work Area. Methods: A quantitative approach was employed using a correlational analytic design with a cross-sectional framework. The study population consisted of 549 individuals, from which 56 respondents were selected as the sample through purposive sampling. Data collection was conducted using structured questionnaires assessing both the perceived role of health workers and community preventive behaviors. Statistical analysis was carried out using univariate and bivariate techniques to explore the association between variables. Results: The majority of respondents were female, in their early twenties, and had completed senior high school education. Most respondents (88.2%) rated the role of health workers as good, while 82.4% demonstrated good behavior in preventing DHF, including eliminating mosquito breeding sites and maintaining environmental cleanliness. Bivariate analysis revealed a statistically significant relationship between the role of health workers and community behavior in DHF prevention, indicating that greater health worker involvement is associated with improved preventive actions among residents. Conclusion: The findings highlight that the active and effective role of health workers plays a critical role in shaping positive community behavior toward DHF prevention. Strengthening health worker engagement and sustaining community education programs are recommended to reduce DHF incidence in high-risk areas.